2017
DOI: 10.1002/ajmg.a.38418
|View full text |Cite
|
Sign up to set email alerts
|

Treating pediatric neuromuscular disorders: The future is now

Abstract: Pediatric neuromuscular diseases encompass all disorders with onset in childhood and where the primary area of pathology is in the peripheral nervous system. These conditions are largely genetic in etiology, and only those with a genetic underpinning will be presented in this review. This includes disorders of the anterior horn cell (e.g., spinal muscular atrophy), peripheral nerve (e.g., Charcot–Marie–Tooth disease), the neuromuscular junction (e.g., congenital myasthenic syndrome), and the muscle (myopathies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 225 publications
(240 reference statements)
2
91
0
Order By: Relevance
“…As in many other hereditary neuromuscular diseases, genetically sophisticated treatments are under investigation for EDMD. A recent study showed that, at least in cell culture, antisense oligonucleotide‐mediated skipping of exon 5 of LMNA can be successfully used, and, therefore, shows promise as a potential therapeutic approach for patients with dominant mutations in this exon . Other molecular strategies that have a possible role in EDMD, such as adeno‐associated virus (AAV)‐based gene replacement and gene‐editing techniques, have not been formally studied in this disease thus far …”
Section: Managementmentioning
confidence: 99%
“…As in many other hereditary neuromuscular diseases, genetically sophisticated treatments are under investigation for EDMD. A recent study showed that, at least in cell culture, antisense oligonucleotide‐mediated skipping of exon 5 of LMNA can be successfully used, and, therefore, shows promise as a potential therapeutic approach for patients with dominant mutations in this exon . Other molecular strategies that have a possible role in EDMD, such as adeno‐associated virus (AAV)‐based gene replacement and gene‐editing techniques, have not been formally studied in this disease thus far …”
Section: Managementmentioning
confidence: 99%
“…The underlying pathomechanisms of congenital myopathies are reviewed elsewhere . Current and future therapeutic approaches to congenital myopathies are elaborated in other reviews . Gene therapy trials are evolving, in particular in X‐linked myotubular myopathy .…”
Section: Pathogenesis Of Congenital Myopathies and Emerging Therapiesmentioning
confidence: 99%
“…Nusinersen (Spinraza) was approved as the first drug for the treatment of all types of SMA patients by the United States Food and Drug Administration (FDA) in December 2016, and by the (33). There seems to be a pathophysiologic developmental stage of motor neuron loss in animal models, and once motor neuron loss has progressed beyond a critical point it is unlikely to rescue the disease process (59,60). On the other hand, there is a differential sensitivity due to deficiency in SMN protein, motor neurons being vulnerable.…”
Section: Antisense Oligonucleotidesmentioning
confidence: 99%